Realization of Expressing Metaphor of Markobar in Mandailing Natal Wedding Ceremony - Muhammad Ardillah Nasution; Sumarsih . .; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
This research dealt with the Metaphorical Expression of Markobar Traditional Ceremonies in Mandailing Natal. The objectives of this study were: to describe the metaphorical expressions are realize in wedding ceremony ofMandailing Natal. This research applied qualitative research design. The data were collected through observation by taking video recording. The findings of this study showed that: there are four processes of metaphorical expressions, they are: giving someone or something God characteristic, giving animal or nonhuman characteristics of human life, giving characteristic of animal to human, giving an abstract thing concretely. In this case showed that Mandailing Natal culture has its roles and procedures. The ways of realizing metaphor in markobar are by applying some realization of metaphor in markobar wedding ceremony. It was Giving someone or something God characteristic (5) 13.51%,  Giving animal or nonhuman characteristics of human life (17) 45.94%, There were more realization of metaphor used in markobar wedding ceremony because markobar was done to the bless the bridegroom and bride which was conducted in the church and the marriage hall. The markobar wedding ceremony involved more people/guest that was why there were more realization of metaphor used in it.Giving characteristic of animal to human (0) it’s because in mangupa or markobar in the Mandailing ethnic, pronunciation cannot be compared to animals in human life because marriage is very sacred and sacred unless it is used in poetry or rhymes in everyday life. And  Giving an abstract thing concretely (15) 40.54%.